Audiometry Finding in Nasopharyngeal Carcinoma Patients in ENT-HN Department of Mohammad Hoesin General Hospital Palembang 1 June 2016-1 June 2020 - Denny Satria Utama; Sella Vanessa Lie (TALENTA PUBLISHER, 2021)
Introduction: Nasopharyngeal Carcinoma (NPC) is a type of epithelial carcinoma that arises from the nasopharynx mucosal lining that usually develops in the fossa of Rosenmüller. One of NPC’s initial signs is hearing loss. Objective: This study aims to determine the audiometry of patients with nasopharyngeal carcinoma in the ENT-HN department of Mohammad Hoesin General Hospital Palembang 1 June 2016-1 June 2020. Methods: This research is a descriptive observational study with cross-sectional study design using medical records of patients with nasopharyngeal carcinoma at Mohammad Hoesin General Hospital Palembang 1 June 2016 – 1 June 2020 who met the inclusion criteria. Results: From 48 samples, 42 samples (87,5%) were male, and 14 samples (29,2%) were included in the age range of 47-52 years. There were 18 samples (37,5%) suffering from a moderate degree of deafness. NPC patients mostly had conductive hearing loss (72,9%). Most of the sample suffered from bilateral hearing loss (75%). The majority of NPC patients had already been in stage IV (70,8%). It was found that NPC patients with stage IV suffered the most from conductive hearing loss (79,4%). Conclusion: NPC patients from 1 June 2016 – 1 June 2020 at ENT-HN Department of Mohammad Hoesin General Hospital Palembang were mostly male with an age range of 47-52 years who suffered from bilateral moderate conductive hearing loss and had already been in stage IV. It was found that most patients with stage IV of NPC had conductive hearing loss